Mortaria at Schedia (Western Delta, Egypt) - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2022)
Excavations at Schedia, an important center in the western Delta of Egypt, brought to light a very limited number of fragments of ceramic mortaria, imported from Tyrrhenian Central Italy and in one case from northern Syria. An Italian piece and the Syrian one bear stamps of some epigraphic interest. The mortaria found at Schedia are evaluated in the context of mortaria in Egypt.